Water Diffusivity Changes Along the Perivascular Space After Lumboperitoneal Shunt Surgery in Idiopathic Normal Pressure Hydrocephalus - Kikuta, Junko; Kamagata, Koji; Taoka, Toshiaki; Takabayashi, Kaito; Uchida, Wataru; Saito, Yuya; Andica, Christina; Wada, Akihiko; Kawamura, Kaito; Akiba, Chihiro; Nakajima, Madoka; Miyajima, Masakazu; et al. (Frontiers in Neurology, 2022)
Abstract Background: The aim of this study was to evaluate the water diffusivity changes along the perivascular space after lumboperitoneal shunt (LPS) surgery in idiopathic normal pressure hydrocephalus. Methods: Nine patients diagnosed with iNPH (three males and six females, mean age ± SD = 75.22 ± 5.12 years) according to the guidelines for iNPH in Japan were included in the study. Post-LPS surgery, six iNPH patients who exhibited improvement in symptoms were defined as responder subjects, while three iNPH patients who did not were defined as non-responder subjects. We calculated the mean ALPS index of the left and right hemispheres and compared the differences between pre- and post-LPS surgery mean ALPS indices in iNPH patients. In the responder or non-responder subjects, the mean ALPS indices in the pre- and post-operative iNPH groups were compared using Wilcoxon signed rank tests. Next, correlation analyses between pre- and post-operation changes in the mean ALPS index and clinical characteristics were conducted. Results: The mean ALPS index of the post-operative iNPH group was significantly higher than that of the pre-operative iNPH group (p = 0.021). In responder subjects, the mean ALPS index of the post-operative iNPH group was significantly higher than that of the pre-operative iNPH group (p = 0.046). On the other hand, in the non-responder subjects, the mean ALPS index of the post-operative iNPH group was not significantly different compared to the pre-operative iNPH group (p = 0.285). The mean ALPS index change was not significantly correlated with changes in the Mini-Mental State Examination score (r = −0.218, p = 0.574), Frontal Assessment Battery score (r = 0.185, p = 0.634), Trail Making Test A score (r = 0.250, p = 0.516), and Evans’ index (r = 0.109, p = 0.780). In responder subjects, the mean ALPS index change was significantly correlated with Evans’ index in pre-operative iNPH patients (r = 0.841, p = 0.036). Conclusion: This study demonstrates the improved water diffusivity along perivascular space in patients with iNPH after LPS surgery. This could be indicative of glymphatic function recovery following LPS surgery.